The impact of astaxanthin on adverse effects of hyperglycemia induced by STZ in retinal tissue of rat - Mojarrab, Shahnaz; Bahrami, Farideh; Khoshbaten, Ali; Shojaei, Ahmad; Daftarian, Narsis; Salem, Fatemeh; Mohammadi, Mohammad Taghi (Progress in Nutrition, 2019)
Astaxanthin (ATX) is a powerful natural antioxidant belongs to xanthophylls and the aim of this study is to investigate its protective roles on adverse effects of hyperglycemia in retinal tissue. Sixty rats were randomly divided into Controls, and hyperglycemic groups. ATX (20 mg/kg) was administrated over 47 days. After 47 days the final blood glucose concentration and body weight also the expression of vascular endothelial growth factor (VEGF), tumor necrosis factor α (TNF-α) proteins, antioxidant capacity and vessels dimension in ganglionic cell layer (RGC) layer in retinal tissue were measured as well as immunohistochemistry and histopathological assessments. Hyperglycemia-induced decrement in Catalase (CAT) (0.096 ± 0.026) and Glutathione (GSH) (133.80 ± 65.10) activity in retinal tissue but increase Superoxide dismutase (SOD) (15.52 ± 1.36 mU/mg) and Malondialdehyde (MDA) (2.64 ± 0.12) content. Administration of ATX increased the antioxidant capacity in the treated group (p<0.05). An increment in the expression of VEGF and TNF-α and vasodilation were shown in the hyperglycemic groups (p<0.01). Immune and histopathological assessments indicated that the ATX treatment could repair vasodilation in RGC layer vessels and also reduce the TNF-α content in retinal tissue (p<0.05). ATX could repair vasodilation and inflammation presumably because of removal of oxidizing and inflammatory agents in retinal tissue but during 47- day treatment it could not significantly decrease expression of VEGF in retinal tissue of hyperglycemic group.